Plasma immersion ion implantation: Influence on the rotating bending fatigue strength of AA 7050-T7451 aluminum alloy - Minto, Thiago Alexandre [UNESP] (2017)
Failures in structural components due to cyclic loading are associated with the surface damage. The aircraft industry has been searched into the alternative coatings that enhance performance by reducing the environmental impact. Coatings deposited by different surface processes are more or less effective to improve fatigue life of diverse elements. The sulphuric and chromic anodizing methods were applied on AA 7050-T7451 aluminum alloy. The study results were compared with the plasma immersion ion implantation for different experimental parameters. This investigation aims to study plasma immersion ion implantation (PIII) effect on the fatigue life of rotating and bending on AA 7050-T7451 aluminum alloy. Experimental results indicate that the implantation setup of low impact frequency increases the fatigue life and improves the roughness without decrease in the microhardness of base material. The implantation of high impact frequency reduces the fatigue life of base material even more than both anodizing processes.